Zucchini lineages with levels of resistance to ZYMV and SqMV viruses - Beloti, Igor Forigo; Maciel, Gabriel Mascarenhas; Alves, Igor Matheus; Pereira, Lucas Medeiros; Lemes, Ernane Miranda (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Zucchini (Cucurbita pepo L.) is a horticultural plant species of great socioeconomic value in tropical countries such as Colombia and Brazil. The production of zucchini is qualitatively and quantitatively affected by many diseases, especially viruses belonging to the Potyvirus (Zucchini yellow mosaic virus - ZYMV) and Comovirus (Squash mosaic virus - SqMV) groups. The primary strategy to reduce the spread of potentially damaging plant viruses is the development of genotypes with genetic tolerance; however, there are not many zucchini genotypes with multiple tolerance. Therefore, this study evaluated 66 zucchini genotypes to find sources of tolerance to the ZYMV and SqMV viruses. This experiment was conducted in a completely randomized design using genotypes from the germplasm bank of the Federal University of Uberlândia, including the genotypes: Emanuela (common commercial genotype) ‘Tronco Caserta’ (susceptible genotype) and PX 13067051 (resistant genotype). Leaf extracts containing viral particles were used as inoculant, and the distribution of grades of tolerance was recorded at the seedling stage. The lineages UFU-C×UFU-A#18#3;1, UFU-C×UFU-F#19#11;3, UFU-F#4#9;1, and UFU-D×UFU-F#7#21;1 and the Emanuela cultivar are alternatives for the production of new zucchini genotypes or hybrids with tolerance to the viruses ZYMV and SqMV. More severe symptoms were observed, as well as a larger number of susceptible genotypes for the ZYMV virus, indicating that this virus has great potential for causing damage and losses to zucchini crops.